2022
DOI: 10.1155/2022/9227838
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Mycoplasma Pneumonia in Children: A Systematic Review and Meta-analysis of Laboratory Features and Predictors

Abstract: Background. Mycoplasma pneumoniae is a common pathogen of community-acquired pneumonia (CAP) in children. M. pneumoniae infection is usually regarded as a self-limiting disease, but in some special cases, it can also develop into refractory Mycoplasma pneumoniae pneumonia (RMPP). The aim of this study is to analyze the clinical characteristics of CRP (C-reactive protein), LDH (lactate dehydrogenase), ESR (erythrocyte sedimentation rate), D-dimer, neutrophils (%), lymphocytes (%), and lung consolidation in RMPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Early identification of SMPP in young MPP patients is of urgent clinical value. Studies have shown that fever over 10 days, young children, higher D-dimer level, lung consolidation, massive pleural effusion, necrotizing pneumonia, CRP >60 mg/L, LDH >410 IU/L, and extrapulmonary complications can be used as predictors of SMPP (33)(34)(35), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Early identification of SMPP in young MPP patients is of urgent clinical value. Studies have shown that fever over 10 days, young children, higher D-dimer level, lung consolidation, massive pleural effusion, necrotizing pneumonia, CRP >60 mg/L, LDH >410 IU/L, and extrapulmonary complications can be used as predictors of SMPP (33)(34)(35), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…It is present in small amounts in an organism's normal state, and its level increases linearly when infected ( 27 ). Notably, some studies have suggested that both inflammatory mediators are closely associated with MPP and are critical biomarkers for measuring MP infection status and predicting the occurrence of severe and refractory MPP ( 28 , 29 ). Serum CRP and PCT levels are lower after MP infection than after bacterial infection; however, they help predict severe MPP ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to our diagnostic meta-analysis, a risk factor-related meta-analysis by Huang discussed CRP, LDH, D dimer, etc. as risk factors for RMPP, but limited to one qualitative and only seven studies on LDH, with possible search bias ( 45 ). Therefore, we conducted a comprehensive search, we conducted a meta-analysis of the diagnostic efficacy of LDH on RMPP, and performed a subgroup analysis to classify and discuss different LDH thresholds, age, case sources, etc., hoping to better guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%